Steigiamasis Seimas ir jo oratoriai - Kasperavičius, Algis (Lietuvos istorijos studijos, 2003)
On April of 1920, elected Constitutive Parliament term continued till the 6th of October 1922. It worked strenuously; there took place 257 ordinary meetings, which continued for some hours every day. They often ended in the next morning. The most important task of the Constitutive Parliament was to prepare a permanent Constitution of the Lithuanian Republic, but it performed other rules' publishing functions too. It performed the control of executive government institutions of all levels. The education of parliament members was much better than the middle education of Lithuanian citizens, but most of them didn't have university education. However, it wasn't a big imperfection of the just born parliamentary system of Lithuania. A diploma or an academic degree isn't identical to the broad mind and the knowledge necessary for political leaders. It can be acquired in the way of self-education too. Oratorical skills are very important as well.In opposition to other parliaments of the West, there weren't many lawyers in the Lithuanian Constitutive Parliament, but there were oratory skills characteristic of other professions' representatives, who sometimes didn't have both the university degree and secondary education. For example, leaders of social democrats like K. Bielinis and J. Plečkaitis. Next to them, the most eminent orators were social democrats: an engineer S. Kairys, a scientist-chemist V. Čepinskis, a leader of populists M. Sleževičius, and a Christian democrat priest M. Krupavičius. In the constitutive parliament, the Right and the Left differed from each other not only in the matter of social reforms, first of all agrarian reform, but also in their standpoint on Catholic religion and the church's place in the state. Disagreements reached their culmination in 1922 during the discussion about the final wording of the constitution.The offers of social democrats and populists were rejected because the majority of votes were held by Christian democrats. In addition, the Right used not only objective arguments but also demagogy. The Right abstained from voting for the Constitution. It was accepted by Christian democrats and by a few executives of national minorities. The anticlericalism of the Left was one of the causes that influenced the downfall of parliamentary democracy in Lithuania as a result of the revolution in December 1926.Discussions in the Constitutive Parliament showed that its members seriously looked at the work of Constitution preparation, though they were not always able to find compromises. They weren't afraid to express their opinion, and they didn't tremble because of the reaction in Warsaw, Paris, Moscow, or London.